2015
DOI: 10.1042/cs20150312
|View full text |Cite
|
Sign up to set email alerts
|

Insulin growth factor-1 (IGF-1) enhances hippocampal excitatory and seizure activity through IGF-1 receptor-mediated mechanisms in the epileptic brain

Abstract: Insulin-like growth factor-1 (IGF-1) is known to promote neurogenesis and survival. However, recent studies have suggested that IGF-1 regulates neuronal firing and excitatory neurotransmission. In the present study, focusing on temporal lobe epilepsy, we found that IGF-1 levels and IGF-1 receptor activation are increased in human epileptogenic tissues, and pilocarpine- and pentylenetetrazole-treated rat models. Using an acute model of seizures, we showed that lateral cerebroventricular infusion of IGF-1 elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
1
24
1
Order By: Relevance
“…In the present study, the activation of ERK1/2 was found to be attenuated as well when the activity of IGF-1R was inhibited by Linsitinib or shRNA targeted to IGF-1R, suggesting that IGF-1R activation of ERK1/2 contributes to the mechanism by which chondrocytes sense and respond to periodic mechanical stress. Our present observation seems consistent with the reports of IGF-1R modulations and interactions with ERK1/2 in other cell types [30,31]. However, this relationship has not been investigated in chondrocytes under mechanical stimulation.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 83%
“…In the present study, the activation of ERK1/2 was found to be attenuated as well when the activity of IGF-1R was inhibited by Linsitinib or shRNA targeted to IGF-1R, suggesting that IGF-1R activation of ERK1/2 contributes to the mechanism by which chondrocytes sense and respond to periodic mechanical stress. Our present observation seems consistent with the reports of IGF-1R modulations and interactions with ERK1/2 in other cell types [30,31]. However, this relationship has not been investigated in chondrocytes under mechanical stimulation.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 83%
“…On the contrary, the hsa-let-7c over-expression downregulated the level of IGF-1R and decreased the odonto/osteogenic differentiation in IGF-1-treated SCAPs. It is commonly believed that IGF-1 takes actions mostly via IGF-1R2324. These findings indicate that IGF-1, IGF-1R and hsa-let-7c act as a whole especially in the process of cell differentiation.…”
Section: Discussionmentioning
confidence: 88%
“…IGF is a polypeptide mitogen that is similar to proinsulin; therefore, it has an important role in regulating cell proliferation, differentiation and apoptosis and mediates cell growth, synthetic metabolism, glucose reduction and immune regulation ( 18 ). Pinzani and Marra ( 4 ) previously demonstrated that PDGF enhanced the secretion and release of IGF and its binding proteins in rat HSCs and also promoted HSC division and proliferation by stimulating DNA synthesis in cells.…”
Section: Discussionmentioning
confidence: 99%